2018
DOI: 10.1007/s10548-018-0662-7
|View full text |Cite
|
Sign up to set email alerts
|

Resting Motor Threshold, MEP and TEP Variability During Daytime

Abstract: Humans show a variation in physiological processes during the day. To reliably assess (changes in) cortical excitability with transcranial magnetic stimulation (TMS), it is relevant to know the natural variation in TMS readouts during the day. In case of significant daytime variations, this should be taken into account when scheduling (follow-up) measurements. This study aims to evaluate the influence of the time of day on the resting motor threshold (RMT), motor evoked potential (MEP) and TMS evoked potential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 65 publications
(97 reference statements)
3
18
1
1
Order By: Relevance
“…Measurements were conducted at 09.00 AM or 02.00PM and spread evenly between AM and PM. No significant differences in TMS measures were reported between these times of day [37], except a larger TMS-evoked potential 100ms after the stimulus [38]. Soft earplugs were used to reduce the coil click.…”
Section: Transcranial Magnetic Stimulationmentioning
confidence: 99%
“…Measurements were conducted at 09.00 AM or 02.00PM and spread evenly between AM and PM. No significant differences in TMS measures were reported between these times of day [37], except a larger TMS-evoked potential 100ms after the stimulus [38]. Soft earplugs were used to reduce the coil click.…”
Section: Transcranial Magnetic Stimulationmentioning
confidence: 99%
“…For example, in Peinemann's study, the effect of 1800 pulses of rTMS lasted less than 40 minutes . Similarly, Muellbacher et al used 1‐Hz rTMS at 115% rMT intensity for 15 minutes and found significant reduction in motor cortex excitability for more than 30 minutes . In this study, the effect on MEP lasted at least 30 minutes.…”
Section: Discussionmentioning
confidence: 49%
“…9 Similarly, Muellbacher et al used 1-Hz rTMS at 115% rMT intensity for 15 minutes and found significant reduction in motor cortex excitability for more than 30 minutes. 17 In this study, the effect on MEP lasted at least 30 minutes. The effect on rMT did not last 30 minutes, although this may have been due to an insufficient sample size.…”
Section: Discussionmentioning
confidence: 76%
“…The TEP P30 and N100 amplitude standard deviations were significantly higher between individuals within one session than within individuals during the day. 117 Casula et al examined various characteristics of TEP induced by sp-controllable TMS over the M1. Specifically, RMT was measured as an approximation of corticospinal excitability; global mean field power (GMFP) was measured as an approximation of global cortical excitability; and local mean field power was measured as an approximation of local cortical excitability.…”
Section: Single-pulse Tms: M1mentioning
confidence: 99%